2022
DOI: 10.1002/edm2.353
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life of people with type 2 diabetes and its associated factors at a tertiary care clinic in Ningbo, China: A cross‐sectional study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Seven studies ( Al Hayek et al, 2014 ; Barua et al, 2021 ; Carter et al, 2022 ; Gebremariam et al, 2022 ; Gebremedhin et al, 2019 ; Mishra et al, 2015 ; Tran Kien et al, 2021 ) revealed that poorer HRQoL was substantially correlated with longer diabetes duration. According to Carter et al (2022) , T2DM duration of more than 10 years (OR = 6.77) and 5–10 years (OR = 5.56) both remained highly related to lower HRQoL.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies ( Al Hayek et al, 2014 ; Barua et al, 2021 ; Carter et al, 2022 ; Gebremariam et al, 2022 ; Gebremedhin et al, 2019 ; Mishra et al, 2015 ; Tran Kien et al, 2021 ) revealed that poorer HRQoL was substantially correlated with longer diabetes duration. According to Carter et al (2022) , T2DM duration of more than 10 years (OR = 6.77) and 5–10 years (OR = 5.56) both remained highly related to lower HRQoL.…”
Section: Resultsmentioning
confidence: 99%
“…However, those who had T2DM for several years were not satisfied, which could be due to multiple reasons, including boredom with the care that they received or not receiving high‐quality care in subsequent years. The longer duration of T2DM is found to be associated with poor glycemic control, high T2DM‐related complications and comorbidities (and polypharmacy), and low health‐related quality of life; 8 , 28 , 29 , 30 all these issues advocate the need for long‐term high‐quality care. Again, a qualitative study should be able to shed light on the reasons behind such dissatisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, very satisfied (27)(28) and satisfied (19)(20)(21)(22)(23)(24)(25)(26) were combined as satisfied.…”
Section: Data Collection Tool and Proceduresmentioning
confidence: 99%
“…In addition, psychological complications, such as anxiety and depression, are common, affecting psychosocial life and daily functioning and leading to poor quality of life(QoL) [ 4 ]. Relevant research results show that their QoL of diabetes patients is generally low, and the prolongation of diabetes is associated with a decline in QoL [ 5 ]. Impaired QoL can affect individual’s motivation to continue with the treatment, such as reluctance to be hospitalised or refusal to control blood glucose.…”
Section: Introductionmentioning
confidence: 99%